Penguatan Moral Disengagement dalam Hubungan Kepemimpinan Etis Terhadap Kinerja Tugas Karyawan - Surya Mutiara Saragih; Andi Ina Yustina; Christine Novita Dewi (Politeknik Negeri Batam, 2021)
This study analyzes the relationship between ethical leadership and task performance and the moderating effect of moral disengagement. The data in this study were 244 respondents who were taken by conducting a web-based questionnaire for employees in various industries in Indonesia. To process data and test hypotheses, researchers used the SEM-PLS approach. This study found that ethical leadership influences employee task performance. However, the relationship between ethical leadership and employee task performance was found to be positive and significant. This study also found that moral disengagement has a moderating effect, strengthening the relationship between ethical leadership and task performance.